ON SOME REFIREMENTS OF FEJER TYPE INEQUALITIES VIA SUPERQUADRATIC FUNCTIONS - Muhammad Amer Latif (IndoMS, 2011)
In this paper some Fejér-type inequalities for superquadratic functionsare established, we also get renement of some known results when superquadraticfunction is positive and hence convex.DOI : http://dx.doi.org/10.22342/jims.17.2.6.97-122